Women Linguistic Features Used by Elle Evans in The Kissing Booth 2 Movie - Sheila Damota, Ni Putu; Suastra, I Made; Laksminy, Luh Putu (Udayana Journal of Social Sciences and Humanities; Vol 6 No 2 (2022): UJoSSH, September 2022DO - 10.24843/UJoSSH.2022.v06.i02.p01, 2022)
Language makes people understand each other and interact in daily life. Most importantly, language has become an important tool in communication. The way men and women speak is different. They have different features although they speak the same language. The title of this undergraduate thesis is "Women's Language Features Used by Elle Evans in The Kissing Booth 2 Movie". The main purpose of this research was to identify and describe the types of women's language styles and to find out functions and factors of the use of women's language. This research is a descriptive-qualitative study and the primary data were expressions in dialogues related to women's language in the movie. The method that was used to collect the data was the documentation method through the note-taking technique. The data analysis was conducted using the theory proposed by Robin Lakoff (1975). The result of this study showed that not all types of women’s language features were used by Elle Evans in the movie The Kissing Booth 2 Movie. The researcher found eight types of women's language features. They are: lexical hedges or fillers, tag questions, empty adjectives, hypercorrect grammar, super polite form, intensifiers, the avoidance of strong swear words and emphatic stress. The precise color terms and rising intonation on declaratives were not found in Elle's utterances. However, the key problem of Lakoff's theory of women's linguistic features is that apparently, men also use women's speech in their dialogue. Lakoff's theory would have been more interesting if she had considered the use of women's speech used by men and the use of strong swear words used by women in her book.